2020
DOI: 10.3390/catal10111247
|View full text |Cite
|
Sign up to set email alerts
|

Indole C6 Functionalization of Tryprostatin B Using Prenyltransferase CdpNPT

Abstract: Tryprostatin A and B are prenylated, tryptophan-containing, diketopiperazine natural products, displaying cytotoxic activity through different mechanisms of action. The presence of the 6-methoxy substituent on the indole moiety of tryprostatin A was shown to be essential for the dual inhibition of topoisomerase II and tubulin polymerization. However, the inability to perform late-stage modification of the indole ring has limited the structure–activity relationship studies of this class of natural products. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…For N1 ‐ 2 g / 4 g / 7 g , the site of attachment was assigned based on a combination of three factors: a lack of N1 proton signals in all spectra, the chemical shift values of the prenyl methylene group (C1’/H1’=~50/~5 ppm), and HMBC correlations between the prenyl H1’ and the azaindole C2/C7a positions. Meanwhile, the single C2 ‐prenylated product ( C2 ‐ 7 g ) was easily identified by the loss of the associated proton signal in its 1D 1 H spectrum, which largely resembled that of the previously characterized tryprostatin B [28a,30e] . Perhaps the most interesting spectral changes were observed when C3 was the site of prenylation ( C3 C ‐ 4 g / 5 g / 6 g , C3 C R ‐ 7 g ), as these products also showed signs of cyclization and dearomatization as predicted by their absorbance profiles (see Figure S106, Supporting Information).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…For N1 ‐ 2 g / 4 g / 7 g , the site of attachment was assigned based on a combination of three factors: a lack of N1 proton signals in all spectra, the chemical shift values of the prenyl methylene group (C1’/H1’=~50/~5 ppm), and HMBC correlations between the prenyl H1’ and the azaindole C2/C7a positions. Meanwhile, the single C2 ‐prenylated product ( C2 ‐ 7 g ) was easily identified by the loss of the associated proton signal in its 1D 1 H spectrum, which largely resembled that of the previously characterized tryprostatin B [28a,30e] . Perhaps the most interesting spectral changes were observed when C3 was the site of prenylation ( C3 C ‐ 4 g / 5 g / 6 g , C3 C R ‐ 7 g ), as these products also showed signs of cyclization and dearomatization as predicted by their absorbance profiles (see Figure S106, Supporting Information).…”
Section: Resultssupporting
confidence: 53%
“…Given the established cytotoxic activity of tryprostatins A and B [1–2] towards human cancer cell lines, we tested the cytotoxicity of the prenylated Aza‐CyWP analogs against human leukemia K562 cells. However, the results of the cell titer‐blue viability assays [30e] revealed that none of the compounds exhibited cytotoxic effects, even at a concentration of 100 μM. This is most likely due to the decreased lipophilicity of the analogs, which would decrease their ability to enter the cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These included a fluorine atom ( 41 ), a chlorine atom ( 42 ), a methyl group ( 43 ), a nitro group ( 44 ), a methoxy group ( 45 ), and a methylenedioxy group that formed a bicyclic structure by also attaching at the meta-position ( 46 ). Additionally, several members of the library were included based on the utility of their diphosphate products in PT-catalyzed alkylation, which themselves are implicated in various biocatalytic applications. …”
Section: Resultsmentioning
confidence: 99%
“…For example, the two variants’ new or increased ability to phosphorylate analogues bearing chemoselective functionalities (alkynes on 24 and 25 , azides on 18 and 27 , terminal alkenes on 22 , and dienes on 34 ) suggested that they bear additional utility in non-natural isoprenoid synthesis compared to the WT. Furthermore, longer-chain allylic and substituted benzylic diphosphates are known substrates of PT-catalyzed alkylation, which themselves have downstream biocatalytic applications. Alongside their demonstrated utility in drug diversification, the proposed engineering of PTs to accept chemoselective functionalities allows for the coupling of drug molecules to solid supports (for target-fetching studies) and fluoro- or chromophores (for bioimaging). As such, the efficient enzymatic production of the corresponding diphosphates is of great interest.…”
Section: Resultsmentioning
confidence: 99%